Design of Blended learning enhance Digital storytelling in Teacher’s College Students Lao PDR. - Muensopha, Bouala (International Journal of Educational Communications and Technology, 2024)
The research explores the use of blended learning to enhance digital storytelling skills in Teacher’s College students in Lao PDR. The study focuses on the design of a PAKSE model consisting of 5 steps: 1) Plan, 2) Active, 3) Keep, 4) Share, and 5) Evaluate. The research investigates the effectiveness of this model in developing English communication skills, including speaking, listening, reading, and writing, through the creation and sharing of digital stories using various digital tools and platforms. The findings suggest that the use of blended learning can provide students with a flexible and personalized learning experience and improve their communication, creativity, and critical thinking skills. The study highlights the importance of addressing factors such as students’ access to technology, learning preferences, and resources and support when designing PAKSE models to ensure an inclusive and effective learning environment.